The Role of Preoperative Imaging in the Detection of Lateral Lymph Node Metastases in Rectal Cancer: A Systematic Review and Diagnostic Test Meta-analysis. Issue 12 (29th August 2022) - Rooney, Siobhan; Meyer, Jeremy; Afzal, Zeeshan; Ashcroft, James; Cheow, Heok; DePaepe, Katja; Powar, Michael; Simillis, Constantinos; Wheeler, James; Davies, Justin; Joshi, Heman
Abstract : BACKGROUND: Different techniques exist for the imaging of lateral lymph nodes in rectal cancer. OBJECTIVE: This study aimed to compare the diagnostic accuracy of pelvic MRI, 18 F-FDG-PET/CT, and 18 F-FDG-PET/MRI for the identification of lateral lymph node metastases in rectal cancer. DATA SOURCES: Data sources include PubMed, Embase, Cochrane Library, and Google Scholar. STUDY SELECTION: All studies evaluating the diagnostic accuracy of pelvic MRI, 18 F-FDG-PET/CT, and 18 F-FDG-PET/MRI for the preoperative detection of lateral lymph node metastasis in patients with rectal cancer were selected. INTERVENTIONS: The interventions were pelvic MRI, 18 F-FDG-PET/CT, and/or 18 F-FDG-PET/MRI. MAIN OUTCOME MEASURES: Definitive histopathology was used as a criterion standard. RESULTS: A total of 20 studies (1, 827 patients) were included out of an initial search yielding 7, 360 studies. The pooled sensitivity of pelvic MRI was 0.88 (95% CI, 0.85–0.91), of 18 F-FDG-PET/CT was 0.83 (95% CI, 0.80–0.86), and of 18 F-FDG-PET/MRI was 0.72 (95% CI, 0.51–0.87) for the detection of lateral lymph node metastasis. The pooled specificity of pelvic MRI was 0.85 (95% CI, 0.78–0.90), of 18 F-FDG-PET/CT was 0.95 (95% CI, 0.86–0.98), and of 18 F-FDG-PET/MRI was 0.90 (95% CI, 0.78–0.96). The area under the curve was 0.88 (95% CI, 0.85–0.91) for pelvic MRI and was 0.83 (95% CI, 0.80–0.86) for 18 F-FDG-PET/CT. LIMITATIONS: Heterogeneity in terms of patients' populations, definitions of suspect lateral lymph nodes, and administration of neoadjuvant treatment. CONCLUSIONS: For the preoperative identification of lateral lymph node metastasis in rectal cancer, this review found compelling evidence that pelvic MRI should constitute the imaging modality of choice. In contrast, to confirm the presence of lateral lymph node metastasis, 18 F-FDG-PET/MRI modalities allow discarding false positive cases because of increased specificity. PROSPERO REGISTRATION NUMBER: CRD42020200319.